Comparison of Three Traffic Management Plans Showing Shadow and Police Vehicle Effects on Driver Behavior at Highway Single Lane Closures. Issue 9 (September 2020) - Blackman, Ross; Legge, Matthew; Debnath, Ashim Kumar
Lane closures on multi-lane roads require drivers to transition safely to an open lane before passing the worksite. To reduce worker and driver injury risk, truck-mounted attenuators (TMAs) are often used to prevent vehicle work zone intrusions and reduce the severity of collisions. To maximize the efficiency and effectiveness of TMA use, it is necessary to determine how and when they should be deployed as well as the best supporting measures. The current research focuses on the effects of different traffic management plans (TMPs) on driver behavior. Three TMPs at night time highway work zones were examined: (1 ) two tail vehicles in the advance warning area, (2 ) three tail vehicles in the advance warning area, and (3 ) addition of a marked police car with flashing lights in the buffer area downstream of the TMA. Driver response to the different TMPs was assessed by measuring vehicle speeds at three points in the traffic management area and observing lane change and merging behaviors on the approach to the TMA. Analysis showed a positive effect of police presence in the buffer area on driver behavior: TMP3 produced a reduction of 8.4%–12.9% in proportions of vehicles exceeding the speed limit by at least 5 km/h when passing the TMA. TMP3 also appeared to produce a positive effect on merging behavior compared with the other layouts. Use of a third tail vehicle in the advance warning area was not found to produce any additional safety benefit and may have a detrimental effect.